2015
DOI: 10.1590/0100-2945-058/14
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Pós-Colheita E Sensorial De Genótipos De Bananeiras Tipo Prata

Abstract: RESumO-O norte de Minas gerais é grande produtor de banana 'Prata-Anã' irrigada, cultura altamente suscetível ao Mal-do-Panamá. O uso de genótipos resistentes é uma alternativa, mas os frutos devem apresentar características pós-colheita o mais próximo possível da 'Prata-Anã', para melhor aceitação pelos consumidores. O objetivo do trabalho foi caracterizar frutos em pós-colheita, identificar a preferência e a intenção de compra de diferentes genótipos de bananeira tipo Prata. Os genótipos Prata-Anã, BRS Plati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
(12 reference statements)
4
12
1
7
Order By: Relevance
“…Chroma, soluble solids, ph, titratable acidity and ratio of mature fruits did not differ among varieties (table 3). the mean values were: chroma of 48.19, 11.96 °Brix, ph 4.58, titratable acidity of 0.31% and ratio of 39.1 (table 4), similar to those found by Carvalho et al (2011), Oliveira et al (2013), Castricini et al (2015). luminosity (l *) of 'BRS Conquista' banana skin was higher than that of 'BRS Platina', and no statistical difference with the other varieties was observed (table 4).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Chroma, soluble solids, ph, titratable acidity and ratio of mature fruits did not differ among varieties (table 3). the mean values were: chroma of 48.19, 11.96 °Brix, ph 4.58, titratable acidity of 0.31% and ratio of 39.1 (table 4), similar to those found by Carvalho et al (2011), Oliveira et al (2013), Castricini et al (2015). luminosity (l *) of 'BRS Conquista' banana skin was higher than that of 'BRS Platina', and no statistical difference with the other varieties was observed (table 4).…”
Section: Resultssupporting
confidence: 85%
“…the green color was less intense in BRS Platina and Prata-Anã varieties, which are characterized by presenting less intense green skin color than BRS Conquista variety at the point of harvest. Both the degradation of chlorophylls and the synthesis of carotenoids are processes modulated by ethylene during ripening, but the color shade can also be a genetic characteristic, giving different nuances to the fruit skin (CAStRICINI et al, 2015), in addition to being an indication of the point of harvest.…”
Section: Resultsmentioning
confidence: 99%
“…This value is similar to those reported by Bezerra & Dias (2009), who found values between 4.6 (FHIA 18) and 5.1 (PV 03-44), and by Castricini et al (2015), who observed variation from 4.2 (FHIA 18) to 4.71 (Prata Anã).…”
Section: Genotypesupporting
confidence: 91%
“…For hue angle, the BRS Maravilha, PC 0101, FHIA 18 and Grand Naine genotypes showed values between 93.22º and 97.39º, indicating that these genotypes peels are greenish yellow, when ripe. The hue angle allows the visualization of changes in the fruit color during the ripening stage, but genetic variation can also play a role on that, conferring different nuances to the peels (Castricini et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Fruit postharvest characteristics are also an important parameter for evaluating the final quality of produced fruits (Godoy et al, 2016;Reis, Viana, Jesus, Santos, & Oliveira, 2016;Castricini, Santos, Deliza, Coelho, & Rodrigues, 2015). Few studies have looked at new banana cultivars and their nutritional requirements in different soil and climatic conditions; this is necessary because the nutritional requirements of these materials are not always the same as traditionally cultivated bananas.…”
Section: Introductionmentioning
confidence: 99%